2013
DOI: 10.1007/s13277-012-0641-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of KPNA2 correlates with poor prognosis in patients with gastric adenocarcinoma

Abstract: This study aims to investigate the expression and significance of KPNA2 in human gastric adenocarcinoma progression and prognosis. Using immunohistochemistry and real-time reverse transcriptase polymerase chain reaction assay, we identified abnormally elevated expression of KPNA2 in gastric adenocarcinoma tissues compared to paired normal stomach mucosa tissues in 30 patients (p < 0.05). In order to investigate the correlations between KPNA2 and the clinicopathological features of gastric adenocarcinoma, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…As displayed in the search flow diagram (Figure 1) and updated Prisma checklist (Supplementary Table S1), 24 articles published from 2006-2016, which reported at least one of the mentioned outcomes, were included in this meta-analysis [4, 8, 10ā€“31]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As displayed in the search flow diagram (Figure 1) and updated Prisma checklist (Supplementary Table S1), 24 articles published from 2006-2016, which reported at least one of the mentioned outcomes, were included in this meta-analysis [4, 8, 10ā€“31]. …”
Section: Resultsmentioning
confidence: 99%
“…First, KPNA2 might serve as a reliable prognostic marker for solid tumors. In this meta-analysis, we included fifteen different cancer types, including breast cancer [14ā€“17], colorectal cancer [11ā€“13], gastric cancer [10, 18, 19], prostate cancer [8], hepatocellular carcinoma [20, 21], epithelial ovarian carcinoma [4, 31], bladder cancer [27], esophageal squamous cell carcinoma [28], endometrial cancer [26], melanoma [30], OMGCT [25], upper tract urothelial carcinoma [29], meningioma [24], astrocytoma [23], head and neck squamous cell cancer [22]. The overall pooled results from these cancer types indicated that elevated KPNA2 expression was associated with patients' poor OS, TTR, RFS and PFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karyopherin alpha 2 (KPNA2) is one of karyopherin a family, and could form heterodimer with Karyopherin 1 to promote nucleus protein import as an adapter protein [7]. Recent studies have illustrated that KPNA2 might be a critical oncogene and a potential prognostic biomarker in malignant diseases including HCC [8][9][10][11]. Furthermore, KPNA2 knock-down could significantly inhibit HCC proliferation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Karyopherin alpha 2 (KPNA2) is one of karyopherin a family, and could form heterodimer with Karyopherin 1 to promote nucleus protein import as an adapter protein [7]. Recent studies have illustrated that KPNA2 might be a critical oncogene and a potential prognostic biomarker in malignant diseases including HCC [8]ā€“[11]. Furthermore, KPNA2 knock-down could significantly inhibit HCC proliferation [12].…”
Section: Introductionmentioning
confidence: 99%